2016
DOI: 10.3389/fmicb.2016.00322
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Survival Patterns among Escherichia coli O157:H7 Genotypes Subjected to Food-Related Stress Conditions

Abstract: The purpose of this study was to evaluate the resistance patterns to food-related stresses of Shiga toxin producing Escherichia coli O157:H7 strains belonging to specific genotypes. A total of 33 E. coli O157:H7 strains were exposed to seven different stress conditions acting as potential selective pressures affecting the transmission of E. coli O157:H7 to humans through the food chain. These stress conditions included cold, oxidative, osmotic, acid, heat, freeze-thaw, and starvation stresses. The genotypes us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…E. coli O157:H7 is one of the most virulent pathogens responsible for foodborne disease globally. Cattle are the main host for E. coli O157:H7 and outbreaks are frequently attributed to the ingestion of contaminated milk and dairy products of cattle origin [ 14 ]. In 1999, a large-scale E. coli O157:H7 outbreak in China had resulted in 195 hospital admissions due to hemolytic uremic syndrome and 177 deaths [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…E. coli O157:H7 is one of the most virulent pathogens responsible for foodborne disease globally. Cattle are the main host for E. coli O157:H7 and outbreaks are frequently attributed to the ingestion of contaminated milk and dairy products of cattle origin [ 14 ]. In 1999, a large-scale E. coli O157:H7 outbreak in China had resulted in 195 hospital admissions due to hemolytic uremic syndrome and 177 deaths [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…All strains isolated belonged to LSPA‐6 lineage I/II. Interestingly, Elhadidy and Álvarez‐Ordóñez () reported that lineage I/II strains were significantly more resistant to acid, cold and starvation stress than lineage II strains, and this fact could explain this persistence in the environment.…”
Section: Resultsmentioning
confidence: 99%
“…Pathogenicity in humans is inexorably linked to the Stx litres produced by individual STEC strains [15, 16]. Hypervirulent clones, as manifested by increased Stx 2a -litres [17–24], have been associated with STEC subpopulations through phylogenetic, epidemiological, and phenotypic linkage [4, 5, 11, 19, 20, 25–49]. The specific factors responsible for elevated Stx-production in hypervirulent STEC strains are unknown but presumably modulated by a number of biotic and abiotic triggers [6, 8, 50–54].…”
Section: Introductionmentioning
confidence: 99%